Principals Administrative Roles on Teachers Job Performance in Private Secondary Schools in Ilorin South Local Government Area, Kwara State - Ayoku, Oba Baba; Lawal, Mubarak Oluwatoyin (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2024)
The study assessed principals administrative role on teachers job performance in private secondary schools in Ilorin South local government area, Kwara state. The research design used for this study was a descriptive survey of the correctional-type method. The study was guided by 5 purposes with 3 research questions and 2 hypotheses. The population of the study consisted of 180 respondents from private secondary schools. The sample for this study was selected using the Purposive sampling technique. The sample consisted of 30 principals and 150 teachers from 30 private secondary schools in Ilorin South Local Government Area, Kwara State. The researcher's instrument was titled Principals Administrative Roles Teachers Job Performance Questionnaire (PARTJPQ) which was filled by principals and teachers. The study used a 4-point Likert scale questionnaire with a reliability coefficient of 0.87, and descriptive statistics to answer research questions. In contrast, PPMC was used to test null hypotheses at a significance level 0.05. The findings suggest that principal supervisory roles are effective in enhancing teachers' job performance in private secondary schools in Ilorin South Local Government Area, Kwara State. One of the recommendations of this study is the need for School administrators should provide targeted training for principals to improve their supervisory skills, focusing on effective strategies for discipline, record-keeping, and the use of teaching aids.